The Miharamycins and Amipurimycin: their Structural Revision and the Total Synthesis of the Latter. Issue 31 (1st July 2019) - Wang, Shengyang; Zhang, Qingju; Zhao, Yachen; Sun, Jiansong; Kang, Wenjia; Wang, Fei; Pan, Haixue; Tang, Gongli; Yu, Biao
Abstract: The structural puzzle of amipurimycin, a peptidyl nucleoside antibiotic, is solved by total synthesis and X‐ray diffraction analysis, with the originally proposed configurations at C3′ and C8′ inverted and those at C6′, C2′′, and C3′′ corrected. A similar structural revision of the relevant miharamycins is proposed via chemical transformations and then validated by X‐ray diffraction analysis. The miharamycins bear an unusual trans ‐fused dioxabicyclo[4.3.0]nonane sugar scaffold, which was previously assigned as being in the cis configuration. Abstract : Final piece of the puzzle : The structures of amipurimycin and the miharamycins have been resolved using chemical synthesis and X‐ray diffraction analysis. The stereochemistry of amipurimycin has been corrected. The miharamycins have a trans ‐fused dioxabicyclo[4.3.0]nonane sugar scaffold, which was previously assigned as being in the cis configuration.